TANGGUNG JAWAB MENARA STAR TOUR DAN TRAVEL TERHADAP PENGEMBALIAN DANA PENUMPANG PESAWAT YANG BATAL BERANGKAT KARENA PANDEMI COVID-19 - Agnes Bella Bonika; Hayatul Ismi; Setia Putra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
One of the public transportation sectors affected by the COVID-19pandemic is air transportation. Many cities or countries have imposed a lockdownor social distancing system in their area, resulting in almost all flights beingcancelled. This is what causes many prospective passengers to cancel theirdeparture, and there are reports that there have been no refunds or delays inrefunding airplane tickets by airline ticket agents to their customers. Of course,this phenomenon causes the rights of passengers as consumers to not be fulfilled.The purpose of this thesis research is to examine, first, the responsibility of travelagents for canceling passenger plane tickets during the COVID-19 pandemic.Second, the obstacles and efforts of travel agents in carrying out theirresponsibilitiesThis type of research can be classified as sociological-juridical research.With a research location at the Travel Agent Office, Menara Star Tour & Travelis on Jalan Wahid Hasim, Pekanbaru. While the population and sample areparties related to the problem under study. This study used primary andsecondary data sources, and data collection techniques were carried out throughinterviews and a literature review.The results of the research conducted by the author are: First, when aplane ticket cancellation has been made, the Star Tour and Travel Tower will beresponsible for all refunds for plane tickets that have been traded to consumers.There are at least 10 (ten) people who have received flight ticket refunds in theform of cash returns of 100% of the plane ticket price. The airline providesresponsibility by returning 100% of the ticket price value in the form of a voucherand also applying normal regulatory refunds in cash, but with a stated time limit.Second, the obstacles experienced by Menara Star Tour and Travel in returningairplane tickets are due to several factors, namely airline policies, Income thatmust be returned, time required, and the system used. To overcome theseobstacles, Menara Star Tour and Travel has several solutions, such as ensuringthat the refund process is carried out quickly and accurately; providing clear andopen communication to consumers; solving the problem as soon as possible; andproviding responsive customer service.Keywords: Responsibility - Refund - Airline Passengers